Fuel Supplier Selection in Foam Packaging Production Using Analytic Hierarchy Process (AHP) : Case Study of Supboonma Packaging Part., Ltd - Pimdee, Jiranan; Nootawee, Tanisa; Kongwisaisuk, Kanyarat (Journal of Advanced Development in Engineering and Science, 2026)
In this research, the analytical hierarchy process is applied to select the fuel supplier in the production process of foam packaging. The evaluation factors include price, quality, punctuality, reliability, cooperation and service. The decision-making is based on the weight scores calculated by the analytical hierarchy process. According to the research results, the factors can be prioritized from most to least as follows: quality > punctuality > reliability > price > cooperation and service, with the weight scores of 0.43, 0.23, 0.19, 0.08, and 0.07, respectively. When considering the weight score of each fuel supplier, it is found that the fuel supplier no.1 gets the highest weight score of 0.61, compared to other suppliers, indicating that the fuel supplier no.1 can provide products that meet the company’s needs the most, and it is therefore the best choice. This research can be used as a guideline or a tool to help the company make systematic decision.